MEK Inhibitor Augments Antitumor Activity of B7-H3-Redirected Bispecific Antibody - Li, Hongjian; Huang, Cheng; Zhang, Zongliang; Feng, Yunyu; Wang, Zeng; Tang, Xin; Zhong, Kunhong; Hu, Yating; Guo, Gang; Zhou, Liangxue; Guo, Wenhao; Xu, Jianguo; et al. (Frontiers in Oncology, 2020)
Targeting cancer antigens by T cell-engaging bispecific antibody (BiAb) or chimeric antigen receptor T cell therapy has achieved successes in haematological cancers, but attempts to use them to fight solid cancers have been disappointing, in part due to antigen escape. MEK inhibitor had limited activity as a single agent, but enhanced antitumor activity when combined with other therapies, such as targeted drugs or immunotherapy agents. This study aimed to analyze the expression of B7-H3 in non-small-cell lung cancer (NSCLC) and bladder cancer (BC) and to evaluate the combinatorial antitumor effect of B7-H3×CD3 BiAb with MEK inhibitor trametinib. We found B7-H3 was highly expressed in NSCLC and BC compared with normal samples and its increased expression was associated with poor prognosis. Treatment with trametinib alone could induce apoptosis in tumor cell, while has no effect on T cell proliferation, and a noticeable elevation of B7-H3 expression in tumor cells was also observed following treatment. B7-H3×CD3 BiAb specifically and efficiently redirected their cytotoxicity against B7-H3 overexpressing tumor cells both in vitro and in xenograft mouse models, which was synergized by trametinib. While trametinib treatment alone affected tumor growth, the combined therapy increased T cell infiltration and significantly suppressed tumor growth. Together, these data suggest that combination therapy with B7-H3×CD3 BiAb and MEK inhibitor may serve as a new therapeutic strategy in the future clinical practice for the treatment of NSCLC and BC.